Feeding the Ten Billion. Plants and Population Growth - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
L Evans. 1998. 264 pp.ISBN 0 521 64081 4 £11.95 /E18.25Cambridge University PressEdinburgh Building, Shaftesbury Road, Cambridge CB2 2RU, UK.Fax: +44 1223 315 052Email: information@cup.cam.ac.uk